Development of fibre-reinforced concrete mix for manufacturing non-prestressed concrete sleepers. (March 2022) - Shakeri, Ashkan; Remennikov, Alex M.; Neaz Sheikh, M.
Abstract: In this paper, an optimal ultra-high performance fibre-reinforced concrete (UHP-FRC), which is also known as reactive powder concrete (RPC), with high flexural strength was developed to satisfy the demands for manufacturing non-prestressed concrete sleepers. First, a preliminary analysis is performed to estimate the maximum flexural stresses developed within sleepers with typical dimensions under typical train axle loads of 25 and 40 tonnes. After determining the required flexural strength, the optimum mix proportions of the RPC is obtained using the Taguchi method. The effects of four important parameters, i.e., silica fume to cement ratio (SF/C), sand to cement ratio (Sand/C), superplasticizer to cement ratio (SP/C), and water to binder ratio (W/Binder) are investigated. It is found that an optimum RPC mix with maximum flexural strength can be developed using the SF/C ratio of 0.3, Sand/C ratio of 1.2, SP/C ratio of 0.4, and W/B of 0.2. Subsequently, it is proved that the UHP-FRC with 2% of fibres (by volume) satisfies the flexural strength demand determined by the preliminary track analysis. Finally, two different configurations of the non-prestressed concrete sleepers are proposed for two different target tonne axle loads (TALs), 25 TAL and 40 TAL.